(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Scarring of tracheobronchial stenosis due to tuberculosis is a serious sequela of airway tuberculosis but is often diagnosed late due to nonspecific clinical symptoms. Paraclinical tests like chest MSCT and bronchoscopy help diagnose, assess damage, and predict treatment. Methods: Retrospective and prospective cross-sectional description of 81 patients diagnosed and treated for airway narrowing due to tuberculosis at the Central Lung Hospital and Bach Mai Hospital from January 1, 2020 to June 30 /2023. Results: Average age 32; The ratio of women is 4 times that of men. Commonclinical symptoms: Cough (100%), chest pain and tightness 71.6%, difficulty breathing 50.6%, symptoms of tuberculosis infection 46.9%, wheezing 18.5%, wheezing 11%. The most common location of stenosis is left main bronchus 67.9%, right main bronchus: 21%, lobar bronchus: 40.7%, trachea: 18.5%. The commonest subtype was fibrostenotic 63%, edematous-hyperemic type 16%, actively caseating 10%, granular 6.1%, tumor and copper ulcers 2.5%, and nonspecific bronchitic 0%.